SOME CONSIDERATIONS RELATED TO THE IMPLEMENTATION OF NEW ECONOMIC POLICY IN TURKESTAN ASSR - Akbayeva Zebinisa Djaloliddinovna (Journals Park Publishing, 2022)
In 1920s, New economic policy affected on social and economic fields of Turkestan. Learning the history of that period is considered as an actual issue. This article will analyze the process of execution and consequeces of new economic policy in Turkestan ASSR.
Keywords: local people; Turkestan Communist Party; Russian Empire